Hubungan Pariwisata Dengan Perdagangan Internasional Di Indonesia - dewi, kadek desy puspita; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 1 (2022): VOL 11 NO 1, JANUARI 2022 [1-403 ]DO - 10.24843/EEP.2022.v11.i01.p09, 2022)
Indonesia has a diversity of tribes and cultures and natural beauty that attracts foreign tourists to visit Indonesia. With the number of foreign tourists increasing in number every year also encourages international trade, and triggers the development of tourism support sectors such as hotels, restaurants, cafes and others. In addition, the role of the government is very instrumental in making policies and updating infrastructure in Indonesia. The objectives to be achieved in this study are: to know the relationship between tourism and international trade in Indonesia. The analysis technique used in this study is the Grangger Causality Test Analysis. The results of this study are the absence of a two-way relationship between tourism and international trade in Indonesia. The government needs to provide facilities or facilities for foreign especially to shopping for local products. Facilities or practical, for example in the form of tax refunds, are enforced at all gates of international exit